Transparent Things: A Cabinet - Hanson, Aubrey Jean, 1979- (Indigenous studies series., 2020)
Literatures, Communities, and Learning: Conversations with Indigenous Writers gathers nine conversations with Indigenous writers about the relationship between Indigenous literatures and learning, and how their writing relates to communities. Relevant, reflexive, and critical, these conversations explore the pressing topic of Indigenous writings and its importance to the well-being of Indigenous Peoples and to Canadian education. It offers readers a chance to listen to authors' perspectives in their own words. This book presents conversations shared with nine Indigenous writers in what is now Canada: Tenille Campbell, Warren Cariou, Marilyn Dumont, Daniel Heath Justice, Lee Maracle, Sharron Proulx-Turner, David Alexander Robertson, Richard Van Camp, and Katherena Vermette. Influenced by generations of colonization, surrounded by discourses of Indigenization, reconciliation, appropriation, and representation, and swept up in the rapid growth of Indigenous publishing and Indigenous literary studies, these writers have thought a great deal about their work. Each conversation is a nuanced examination of one writer's concerns, critiques, and craft. In their own ways, these writers are navigating the beautiful challenge of storying their communities within politically charged terrain. This book considers the pedagogical dimensions of stories, serving as an Indigenous literary and education project.